2021
DOI: 10.1021/acs.jpclett.1c01917
|View full text |Cite
|
Sign up to set email alerts
|

How a Quantum Computer Could Quantify Uncertainty in Microkinetic Models

Abstract: A method of uncertainty quantification on a quantum circuit using three samples for the Rh(111)-catalyzed CO oxidation reaction is demonstrated. Three parametrized samples of a reduced, linearized microkinetic model populate a single block diagonal matrix for a quantum circuit. This approach leverages the logarithmic scaling of the number of qubits with respect to matrix size. The Harrow, Hassidim, and Lloyd (HHL) algorithm for solving linear systems is employed, and the results are compared with the classical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…Reiher et al [Reiher et al, 2017] propose to calculate the reaction mechanisms by implementing a multi-configurational wave function as a sub-model to be solved on a quantum computer to improve/enhance classical methods such as density functional theory (DFT). Apart from enzyme design Cheng et al [2020], these kind of computational studies of reaction mechanisms and kinetics can be found for a wide area of high impact applications such as green catalysis of the Mannich reaction Stevens [2017], biochemical redox reactions [Jinich et al, 2019] and calculating uncertainties in microkinetic models Becerra et al [2021].…”
Section: Biochemical Applicationsmentioning
confidence: 99%
“…Reiher et al [Reiher et al, 2017] propose to calculate the reaction mechanisms by implementing a multi-configurational wave function as a sub-model to be solved on a quantum computer to improve/enhance classical methods such as density functional theory (DFT). Apart from enzyme design Cheng et al [2020], these kind of computational studies of reaction mechanisms and kinetics can be found for a wide area of high impact applications such as green catalysis of the Mannich reaction Stevens [2017], biochemical redox reactions [Jinich et al, 2019] and calculating uncertainties in microkinetic models Becerra et al [2021].…”
Section: Biochemical Applicationsmentioning
confidence: 99%
“…This scenario above is known as a reduced kinetic model. 19,31 In eqn (7a) and (7b), two reacting species and one inert species are modeled. H 2 association is connected with the rate constant k 5 , and O 2 dissociation is connected with the rate constant k À6 .…”
Section: Jacobian Linearized Ode Modelmentioning
confidence: 99%
“…Each MK model integration takes a few minutes to complete. Additionally, large MK models are often sensitive to the initial operating conditions (Becerra et al, 2021), i.e., small perturbations in initial conditions can cause large changes in the output. Therefore, we anticipate a MK model embedded in process flowsheet with recycle loops would need to be integrated tens to hundreds of times to converge the flowsheet in sequential modular simulation environments (e.g., AspenPlus) which would make process simulation or optimization cumbersome and computationally intensive.…”
Section: Mk Model Reductionmentioning
confidence: 99%